"Liberation" as a political horizon amidst the coronavirus pandemic in the United States. Issue 3 (November 2020) - Crane, Nicholas Jon; Pearson, Zoe
Participants in diverging US-based protest waves during the coronavirus pandemic are invoking "liberation" as a political horizon. Especially visible are superficially libertarian protests against government "stay-at-home" orders, on the one hand, and, on the other, racial and economic justice organizing around uneven exposure to the deadly effects of the pandemic. Beginning in May 2020, the latter articulation of liberation was amplified by widespread protest against racist police violence. The coronavirus pandemic is putting into sharp relief the contradictions of "liberation" promoted by individualists and underscoring the urgency of organizing for emancipatory social solidarity.